Exploring Students’ Perceptions of WordWall Use for Vocabulary and Pronunciation Development in an EFL Boarding School Classroom - Utami, Erina Aulia; Lausiry, Ditha Andini; Nursyafiq, Nursyafiq (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This research explored students’ perceptions of the use of a WordWall as an educational tool in an English as a Foreign Language classroom within a boarding school setting. The focus was on students' perceptions about how the WordWall aids in vocabulary growth, awareness of pronunciation, and motivation to learn. A qualitative case study approach was taken, involving 42 students in the seventh grade and an English teacher from an Islamic junior high school that functions under a boarding system. Data were gathered through questionnaires and semi-structured interviews, which were analyzed using descriptive percentages and qualitative descriptive analysis methods. The results showed that students had a generally positive outlook on the WordWall as a learning aid. Most of the participants indicated that the WordWall helped enhance vocabulary skills, raised awareness of pronunciation, and promoted higher participation in class activities. Additionally, the results suggested that the WordWall helped boost students’ motivation and involvement in learning English. Consequently, the WordWall can be considered a useful visual educational tool that supports both language acquisition and student engagement in EFL classrooms. Keywords: Vocabulary, Pronunciation, Word wall, Perception